Design and advanced computational approaches based comprehensive structural parametric investigations of rotary-wing UAV imposed with conventional and hybrid computational composite materials: A validated investigation - Raja, Vijayanandh; AL-bonsrulah, Hussein A. Z.; Gnanasekaran, Raj Kumar; Eldin, Sayed M.; Rajendran, Parvathy; Baskaran, Balamurali; Sakthivel, Pradesh (Frontiers in Materials, 2023)
This work aims to design a rotary-wing unmanned aerial system (RUAS) that monitors the pollutants and minimizes their concentration in the atmosphere. This RUAS could be well suited for implementation in cities such as New Delhi and Ghaziabad, where air pollution is a major concern. This RUAV's well-thought-out design and use would be good for the environment also a step forward in the technology of UASs. Therefore, an advanced approach in design as well as innovative computational composite materials development based on structural analysis of this RUAS has been made. The major components involved in this comprehensive investigation are the fuselage, main rotor and tail rotor of RUAS. The aerodynamic parameters on RUAS have been estimated through the advanced technique adopted computational fluid dynamics approach using ANSYS Fluent 17.2. The finite element analysis (FEA) of the RUAS imposed under two different approaches enforced on lightweight composite materials has been estimated through ANSYS Structural 17.2. Firstly, the advanced computational platform for the development of composite materials has been created through the ANSYS Composite Preprocessor tool 17.2, wherein computational moldings of the fuselages of RUAV are framed. The computational moldings are greatly supported and so the conventional polymer matrix composites, metal matrix based composites, and advanced hybrid composites are well prepared. All of these uniquely framed materials have undergone computational structural investigations, and the material suitable for RUAVs has thus been selected. The computational tests are validated with advanced experimental outcomes, which further enhanced this proposed work's reliability. Additionally, the main rotor and entire RUAV are also computationally investigated under aerodynamic loading conditions through fluid structure interaction (FSI) approach. At last, the suitable lightweight material for all the parts of RUAS is shortlisted through innovative integrated computational engineering analyses.